Dictionary of gestures : expressive comportments and movements in use around the world - Caradec, François; Cousin, Philippe; Clarke, Chris (The MIT Press, 2018)
"This is an illustrated dictionary of over 850 gestures from around the world. Gestures often convey meanings that transcend borders, but sometimes they bear vastly different meanings from one continent to another. A dictionary, then, of bodily signs made voluntarily in order to communicate in a open manner: not sign language, no involuntary psychoanalytic "tells," no dance moves, and no secret means of exchange (for example, the recent appropriation of the same "a-ok" gesture mentioned above by white supremecists) or professional codes (military, for example). Which is not to make this book sound limited, but rather to explain that the overall guiding principle is the way we go about joining words to gestures throughout the world in our everyday lives (gestures don't constitute a language in and of themselves), with a side interest in the fact that there are no universals in the realm of the gesture. All entries are illustrated in a how-to manner via drawings (utilizing men, women, and children from all cultures, reflecting the book's global coverage), while illustrations from other sources showing gestures being performed in various cultural contexts throughout history are also scattered throughout the book and the introduction. Entries are organized by body parts and body regions, from head to foot (with everything in between: chin, nose, thumb, buttocks, and 33 other body parts), with an index for intention and interpretation of the different gestures (i.e., Complicity, Despair, Homosexuality, Indifference, Satisfaction, and so on) that makes for a different means of taxonomy"--
Keywords: sanakirjat; kielioppaat; semiotiikka; elekieli; ruumiinkieli